Analisis Kelompok Kegiatan Masyarakat Sempadan Sungai dalam Hubungannya dengan Upaya Menjaga Kebersihan Sungai di Wilayah Kelurahan Sungai Lulut Kecamatan Banjarmasin Timur Kota Banjarmasin Provinsi Kalimantan Selatan: The Analysis of the River Border Community Activity Groups concerning Efforts to Maintain the River Cleanliness in the Sungai Lulut Village Area, East Banjarmasin District, Banjarmasin City, South Kalimantan Province - Amani, Mukhyar; Ramadhan, Damang Jati; Mahyuni, Basuki Rahman (Media Ilmiah Teknik Lingkungan (MITL), 2024)
Sungai Lulut sub-district is one of the sub-districts within the East Banjarmasin sub-district, Banjarmasin City. Most of the daily activities of the river border communities in this sub-district consist of market and shop activities. It is thought that population density and the rise of trade activities can affect the cleanliness of rivers. At least two types of waste were found on the river border of Sungai Lulut Village, East Banjarmasin District, namely domestic waste and commercial waste. There are indications of a relationship between community activity groups and efforts to deal with waste and rubbish, thus showing their influence on community efforts to maintain river cleanliness. It is also indicated that the age and education level of the community are influencing factors, as can be seen from the student-level community groups whose involvement is relatively low in efforts to deal with waste to keep the river clean.